Silent giant: A case report of retroperitoneal schwannoma (Indian Journal of Case Reports, 2024)
Schwann cells of the peripheral nerve sheath give birth to soft-tissue tumors known as schwannomas (neurilemmomas). Schwannomas of the retroperitoneum are uncommon. Diagnosis is frequently delayed in view of unspecific clinical symptoms and non-typical radiologic findings. The preferred course of therapy is total surgical excision. The prognosis is favorable; however, further monitoring is required due to the possibility of recurrence and malignant change. In this case report, we describe a case of retroperitoneal schwannoma in a 44-year-old male and examine the pertinent research.